Dermatological presentations to a regional Victorian hospital emergency department: A 1‐year audit. (20th October 2022) - Ronaldson, Claire; Zhou, Kelly; Lam, Michael; Ong, Dillon; Morgan, Sian; Sathe, Aditya; Isaacs, Anton N.
Abstract: Objectives: The objective of this study is to describe the epidemiological features of each presentation with a primary dermatological diagnosis to a regional emergency department (ED). Design: 1‐year retrospective audit. Setting: Regional Victorian hospital emergency department. Participants: Any presentation to this regional emergency department with a dermatological condition from 1 January 2020 to 31 December 2020. Main Outcome Measures: Dermatology presentations to the ED in 2020 and the prevalence of the associated primary diagnosis. Results: In total, 4.7% ( n  = 1873) of ED presentations had a primary dermatological diagnosis. Of these, 1484 were ≥18 years of age and 389 were ≤17 years of age. Cellulitis (26.1%, n  = 388) was the most common primary diagnosis among presentations ≥18 years. Non‐specific rash was the most common diagnosis (23.6%, n  = 92) in presentations ≤17 years. Indigenous Australians ≥18 years were more likely to be in a younger age group ( p  < 0.01), and dermatitis/eczema presentations ≥18 years ( n  = 10) were the largest diagnostic group referred to a dermatologist. A total of 134 (7.1%) patients ≥18 years travelled more than 50 km to the ED. There were no dermatological emergencies identified. Conclusions: A high proportion of presentations to this regional ED with a dermatological diagnosis could be well managed by a dermatologist or general practitioner (GP) as an outpatient. The findings of this study inform the need for future rural public dermatology services. Options include teledermatology, or a public weekly or fortnightly rapid review dermatology clinic with a visiting dermatologist, in the absence of a dermatologist onsite.